Acute effect of taping on plantar pressure characteristics in athletes with exercise-induced leg pain: a description and comparison of groups - Park, JM.; Kim, T. (The Physician and Sportsmedicine, 2019)
Objectives: Foot pronation is considered as a potential risk factor of lower leg overuse injury. This study aimed to identify plantar pressure characteristics of elite athletes with exercise-induced leg pain in throwing athletic disciplines, and to verify the acute effect of taping for restricting foot pronation by analyzing the plantar pressure characteristics.